A SURVEY OF ANCIENT TURKIC LITERATURE IN 19TH CENTURY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
In the X-XII centuries, literature in the Turkish language developed significantly. A number of poets and writers came out. Yusuf Khos Hajib is one of them. The author's name is Yusuf. There is very little information about him. Some information can be found in "Kutadgu Bilig". He wrote this work in 462 AD (1069-1070) when he was 50 years old. Yusuf gives the following information about himself in the preface of the work: "Balasagun mavludlio, who classified this book, is a Parqiz idisi er turur.